2016
DOI: 10.1371/journal.pone.0168966
|View full text |Cite
|
Sign up to set email alerts
|

Novel Candidate Genes and a Wide Spectrum of Structural and Point Mutations Responsible for Inherited Retinal Dystrophies Revealed by Exome Sequencing

Abstract: BackgroundNGS-based genetic diagnosis has completely revolutionized the human genetics field. In this study, we have aimed to identify new genes and mutations by Whole Exome Sequencing (WES) responsible for inherited retinal dystrophies (IRD).MethodsA cohort of 33 pedigrees affected with a variety of retinal disorders was analysed by WES. Initial prioritization analysis included around 300 IRD-associated genes. In non-diagnosed families a search for pathogenic mutations in novel genes was undertaken.ResultsGen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 58 publications
2
42
0
1
Order By: Relevance
“…Several studies have linked CEP78 ‐truncating variants with a unique CRDHL phenotype and, so far, all described variants are frameshift or splice site sequence variants with a presumed LOF effect. Recently, a homozygous structural variant affecting CEP78 , that is, a deletion‐inversion‐deletion, has also been described in a patient with CRDHL (Table S13; Fu et al, 2016; Namburi et al, 2016; Nikopoulos et al, 2016; Sanchis‐Juan et al, 2018; de Castro‐Miró et al, 2016). Here, we report the first missense variant causing CRDHL, c.449T>C, p.(Leu150Ser), expanding the CEP78 molecular spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have linked CEP78 ‐truncating variants with a unique CRDHL phenotype and, so far, all described variants are frameshift or splice site sequence variants with a presumed LOF effect. Recently, a homozygous structural variant affecting CEP78 , that is, a deletion‐inversion‐deletion, has also been described in a patient with CRDHL (Table S13; Fu et al, 2016; Namburi et al, 2016; Nikopoulos et al, 2016; Sanchis‐Juan et al, 2018; de Castro‐Miró et al, 2016). Here, we report the first missense variant causing CRDHL, c.449T>C, p.(Leu150Ser), expanding the CEP78 molecular spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, seven different truncating mutations have been reported in CEP78 , segregating in CRDHL families of different origins (Fu et al, 2016; Namburi et al, 2016; Nikopoulos et al, 2016). Furthermore, a homozygous CEP78 ‐truncating variant was found in a family with reported nonsyndromic RP (MIM# 268000; de Castro‐Miró et al, 2016). So far, only frameshift and splice site variants have been identified, with the latter all displaying exon skipping at the RNA level (Fu et al, 2016; Namburi et al, 2016; Nikopoulos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Paired-end multiplex libraries, sequence enrichment, base read pairs, base calling, quality control and data processing were performed with the Illumina RTA sequence analysis pipeline as previously described 9. The results were mapped to the human genome assembly GRCh37.75 and annotated against Human dbSNP V. 137 IDs, population frequencies from the 1000 Genomes Project10 and Exome Variant Server,11 and several conservation and pathogenicity prediction algorithms from dbNSFP12 using snpSift 13…”
Section: Methodsmentioning
confidence: 99%
“…The PCR and sequencing primers are available on request. Pathogenicity scores for the variants identified were evaluated by several prediction algorithms (eg, MutationTaster, PolyPhen2, SIFT and NetGene2) as described elsewhere 9. Pathogenicity was also assessed by cosegregation analysis in the family.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that NGS of gene panels leads to higher detection of a genetic cause for retinal disease than traditional methods such as Sanger sequencing; however, these studies often have features that do not reflect clinical practice and may prevent extrapolation of reported diagnostic rates to clinical practice. Some studies recruited patients and often their families, while others heavily weighed in silico predictions for classifying missense variants as pathogenic and only one of these studies took into account American College of Medical Genetics and Genomics (ACMG) criteria for classifying variants, which puts low value on in silico predictions (Audo et al, ; Bernardis et al, ; Carss et al, ; de Castro‐Miro et al, ; Glockle et al, ; O'Sullivan et al, ; Riera et al, ). Some studies investigated only subsets of patients or patients with well‐defined phenotypes (Audo et al, ; Licastro et al, ; O'Sullivan et al, ).…”
Section: Introductionmentioning
confidence: 99%